Validating the reproductive tract score (RTS) technique in pre-service buffalo heifers - Freddys Escalona-Ramírez; Jessenia Mercado-Carrillo; Balbino A. Jaimes-Vazques; Antonio Landaeta-Hernández (Revista Científica)
The fast growth of buffalo (Bubalus bubalis) herds has placed this livestock species as a suitable alternative for animal protein production in the Venezuelan tropics. As with any domestic species with food production interest, the buffalo’s reproductive performance has a paramount relevance, which may be improved by applying the technique of reproductive tract scores (RTS). Using rectal palpation, the RTS (scale 1-5) assign the following scores: 1=flabby uterus and ovaries both <10 mm of diameter with no detectable follicles; 2=flabby uterus and ovaries both 10-15mm of diameter with <8 mm follicles; 3=soft tone uterus and ovaries both <15-20 mm of diameter with 8-10 mm follicles; 4=good tone uterus with 20-25 mm of diameter, ovaries >20mm with >10 mm follicles; 5= good tone uterus >25 mm of diameter, ovaries >20mm with evident luteal tissue. Therefore, the objective of this study was to validate the technique of RTS in pre-service buffalo heifers as a management strategy to improve the pregnancy rate. One-hundred and ten buffalo heifers with ages of 27 + 3 months and body weight of 354,32 + 24,14 kg were assessed for RTS before starting a breeding season of 120 days (Sep-Dec 2020) with four buffalo bulls in a proportion male to female 1:30. 67% of buffalo heifers were found with RTS among 3-5 (mature tract), while 33% were found with RTS among 1-2 (immature tract). Pregnancy was diagnosed 60 days after the end of the breeding season. Data was analyzed by Logistic Regression. A linear and positive increase association (p<0.02) was observed between RTS and pregnancy rate (RTS=5:85%, RTS=4:80%, RTS=3:74%, RTS=2:62%, and RTS=1:50%) indicating a beneficial effect of reproductive tract maturity on pregnancy rate. Likewise, body weight at service and pregnancy rate were also associated (p<0.0001). It was concluded that RTS is a good predictor of pregnancy rate in buffalo heifers. Thus, applying RTS at a field level should be a beneficial management tool.